A Novel Approach of Cloud Security by Authentication in Cloud Computing Environment - Sardana, Vaibhav; Saxena, Nidhi (International Journal of Computer Sciences and Engineering, 2019)
Now a days Internet grows up rapidly. Anything depends on network. This internet provide huge services to the users like data transfer, uploading, downloading etc… some of network services also provide security too. But here data storage is major task, its highly impossible to store huge data in network. Now the new emerging technology is cloud computing, its improve the performance, scalability and low cost to implement. Its provides many services to clients. Like upload the data retrieve the data etc… many organizations are depends on this storage service. We can install the cloud private or public or both. But cloud computing suffer from unauthorized data access. Still there is no permanent solution. These paper main objects are a) Prevent from unauthorized access b) prevent unnecessary steps to access the cloud c) To apply some tasks on cloud.